Deposição e uniformidade de distribuição da calda de aplicação em plantas de café conilon utilizando a pulverização pneumática - Calvi, Deangelys Petene (2015)
Chemical control has been contributing for years to increase productivity in several crops, but is the victim of constant bias by causing contamination to the environment, applicators and especially the food. The use of pneumatic spray gun type is commonly challenged by present lack of uniformity in the deposition and high susceptibility to drift and evaporation of the droplets. Still in coffee of the Espírito Santo, Brazil, in the applications of fungicides, insecticides and foliar fertilizers has increased the use of this implement, mainly by adjusting well to land with rugged terrain, and good operating performance. This study aims to evaluate the uniformity of droplet deposition in conilon coffee plantation and the syrup penetration capacity within the plant using a pneumatic spray at three speeds. The experiment was a farm with three years old, average height of 1.6 m in a randomized design, factorial (6x3x3) with six planting rows spaced at 3.5 m, three different speeds (5.4 km h -1 , 7.8 km h-1 and 10.5 km h-1 ) and three evaluation positions on the plant (front, rear and internal to the sprayer). The spray solution was prepared with bright blue food dye (FD & C # 1) and 1,500 mg L-1 after application were collected four sheets of each installment and washed the laboratory for analysis in spectrophotometer for subsequent calculation of the deposition. To compare the means we used the Tukey test at a level of 5% probability. The wind speed at the time the application was 1.1 m s -1 , relative humidity of 87% and a temperature of 21.7°C. The speed of 7.8 km h-1 appears to be the most suitable for the use of pneumatic spray; however, spraying was low uniformity with greater deposition on the first and third rows, and reduced syrup tank to the extent that the distances are increased, in addition to the low potential syrup penetration in the plant canopy.